Effect of Different Plant Extracts on Post-Harvest Quality and Shelf Life pf Banana (Musa acuminata CV. Grand Naine) - Ghimire, Nabin; Subedi, Badad; Upreti, Ramesh (Journal of Agriculture and Resource Management, 2024)
Banana is a valuable agricultural product with rising demand over time. However, managing post-harvest losses is a significant challenge due to the highly perishable nature of bananas, which makes them prone to rapid deterioration. An experiment was conducted at the Horticulture Laboratory of the School of Agriculture, Far-Western University during March, 2023 to assess the effect of various plant extracts on quality and shelf life of banana. The experiment used a completely randomized design (CRD) with five treatments: guava leaf (T1), lemon juice (T2), neem leaf (T3), eucalyptus leaf (T4), and a non-treated control (T5), each with four replications. Data were collected from 6 destructive and 6 non-destructive banana samples at 3-day intervals, and analyzed using R studio V 1.1. The study revealed that the plant extracts did not affect banana quality parameters on 3 days but showed significant influence after extended storage. Among the different post-harvest treatments, eucalyptus showed the lowest physiological loss in weight (17.44% ), least total soluble solid (16.25),highest tritratable acidity (0.66), highest firmness at (3.02 kg/cm2) until 15 days and declined slightly to (2.75 kg/cm2) at 18 days, highest (24.60 ) shelf life, long (16.0 ) days of ripening. While the highest physiological loss in weight (21.14%) and least shelf life (14) was recorded in control. As a result, plants extracts, especially eucalyptus can be utilized to increase the storage life of banana. Hence the study clearly depicted that post-harvest treatments using different plant extracts could be beneficial to prolong the shelf life of banana.